2014
DOI: 10.1080/01932691.2014.956114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Action ofFuntumia elasticaExtracts on the Corrosion of Q235 Mild Steel in Hydrochloric Acid Medium: Experimental and Theoretical Studies

Abstract: The inhibiting effect of aqueous extracts of Funtumia elastica (FE) on mild steel corrosion in 1 M HCl solution was investigated using electrochemical and surface characterization techniques. The results revealed that FE effectively inhibited the corrosion reaction. Polarization data reveal that the extract functioned as a mixed-type inhibitor, while impedance results show that the extract organic matter adsorbed on the metal/solution interface. FT-IR, SEM and AFM results confirmed the formation of a protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A thorough examination of the plots revealed that in 1.2 M H 2 SO 4 and 0.3 M H 2 SO 4 acid concentrations, the existence of BKL in the test solution pushed the anodic and cathodic side to the minimum current values. 38 It is evident that the BKL extract obstructed the anodic and cathodic sites from further reactions. The electrochemical variables, namely corrosion potential E corr , and corrosion current densities i corr generated from this experiment are listed in Table 6.…”
Section: Potentiodynamics Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough examination of the plots revealed that in 1.2 M H 2 SO 4 and 0.3 M H 2 SO 4 acid concentrations, the existence of BKL in the test solution pushed the anodic and cathodic side to the minimum current values. 38 It is evident that the BKL extract obstructed the anodic and cathodic sites from further reactions. The electrochemical variables, namely corrosion potential E corr , and corrosion current densities i corr generated from this experiment are listed in Table 6.…”
Section: Potentiodynamics Polarizationmentioning
confidence: 99%
“…[43][44] Constant phase element (CPE) is employed to substitute a capacitor to envisage the shifting mechanism due to the dark densely flakes on the electrode. The impedance of the CPE is denoted by: 38 Z CPE = Q -1 (jw) -n (13) where Q and n are associated with CPE and exponent, respectively, j 2 = -1 is regarded as the imaginary axis, ù stands for angular frequency in rads -1 , (ù = 2ðf explains the frequency in H Z ), R S signifies solution resistance, W denotes the impedance factor and n is the considered shifting factor which explains the surface heterogeneity, impurities and surface fractions of the metal. 45 Addition of BKL extract in the blank solution assisted in promoting the radius of the imperfect circle, which denotes the impeding of the corrosion, and it corresponds to R ct of the steel surface.…”
Section: Electrochemical Impedance Studymentioning
confidence: 99%
“…As a result, it follows that the limitation of corrosion action under the influence of acidic conditions and the presence of chloride ions are significant issues deserving of thorough research [143]. Several plant extracts, including Funtumia elastica [144], Musa paradisica [145], watermelon rind [146], Pimenta dioica [147], Thymus vulgaris [148], Cissus quadrangularis [149], Polygonatum odaratum [150], Ircinia strobilina [151], Tithonia diversifolia [152] and Boscia senegalensis [153], are used as corrosion inhibitors in 1M HCl. The combination of diethyl ether and ethyl acetate at 0.5 g/L was found to have the maximum IE when the corrosion inhibition activity of Ptychotis verticillate [154] was examined for MS, and it had respective conversion rates of 75% and 86%.…”
Section: Comparative Analysis 61 Comparison Of 1m Hcl Conc Of Acidmentioning
confidence: 99%
“…The chemistry of plant species belonging to the genus Funtumia is not well documented when compared to that of the renowned Rauvolfia and Tabernaemontana genera (~76 and 110 species respectively) [15,16]. However, previous studies on Funtumia species report the isolation of various classes of secondary metabolites including alkaloids, sterols, acid J o u r n a l P r e -p r o o f derivative (ascorbic acid) and an ursane triterpene (methyl ursolate) with potent, antiplasmodial activities [11,[17][18][19].…”
Section: Leishmaniasis Is Among the Top Five Of Vector-bone Diseases ...mentioning
confidence: 99%